The classification of control problems the development of higher education - Чередниченко, Ольга Юрьевна; Рябко, Ольга Васильевна (Eastern-European Journal of Enterprise Technologies, 2010)
The hierarchical distributed structure of higher education system was considered. The basic consumers for higher education system are allocated: the state, the market, a society. The classification of control problems on the basis of various criteria was developed.